Pathways to high and low performance: factors differentiating primary care facilities under performance-based financing in Nigeria. Issue 1 (25th October 2017) - Mabuchi, Shunsuke; Sesan, Temilade; Bennett, Sara C
Abstract: The determinants of primary health facility performance in developing countries have not been well studied. One of the most under-researched areas is health facility management. This study investigated health facilities under the pilot performance-based financing (PBF) scheme in Nigeria, and aimed to understand which factors differentiated primary health care centres (PHCCs) which had performed well, vs those which had not, with a focus on health facility management practices. We used a multiple case study where we compared two high-performing PHCCs and two low-performing PHCCs for each of the two PBF target states. Two teams of two trained local researchers spent 1 week at each PHCC and collected semi-structured interview, observation and documentary data. Data from interviews were transcribed, translated and coded using a framework approach. The data for each PHCC were synthesized to understand dynamic interactions of different elements in each case. We then compared the characteristics of high and low performers. The areas in which critical differences between high and low-performers emerged were: community engagement and support; and performance and staff management. We also found that (i) contextual and health system factors particularly staffing, access and competition with other providers; (ii) health centre management including community engagement, performance management and staff management; and (iii) community leader support interacted and drove performance improvement among the PHCCs. Among them, we found that good health centre management can overcome some contextual and health system barriers and enhance community leader support. This study findings suggest a strong need to select capable and motivated health centre managers, provide long-term coaching in managerial skills, and motivate them to improve their practices. The study also highlights the need to position engagement with community leaders as a key management practice and a central element of interventions to improve PHCC performance.